What Are Leverage, Company Size, and Social Disclosure Considered to Reduce Market Response to Earnings Response Coefficient as an Intervening Variable? - Taufiq, Abd. Rohman; Oktris, Lin; Saat, Maisarah Mohamed (AKRUAL: Jurnal Akuntansi, 2024)
Introduction/Main Objectives: This research examined the influence of leverage, company size and social disclosure on the earnings response coefficient as an intervening variable. Background Problems: Research showed that leverage ability, company size, and social disclosure influence the earning response coefficient. Furthermore, the company size variable positively influenced ERC in various industrial sector companies on the Indonesian Stock Exchange. Research Methods: This type of research used quantitative methods. The research data was manufacturing companies that were registered with an IPO before 2016 and were still listed on the IDX from 2016 to 2020. For this reason, this regression model was suitable for testing and examining the effect of leverage on the earning response coefficient. Finding/Results: The larger the company size increases the market response because the company was considered capable of providing high returns. The social disclosure variable does not influence ERC in various industrial sector companies on the Indonesian Stock Exchange. Social disclosure was a principle or reaction carried out by companies to participate in community activities in general. This practice causes the company’s asset value and profits low while the debt value and losses were high. Conclusion: High social disclosure was considered to reduce market response. On the other hand, low social disclosure was deemed to increase market response.